Building Character Generation in Elementary Schools Through Education Report Cards: Study in South Sulawesi - Wahira Wahira; Abdul Hamid; Lukman HB (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
Character education based on report card results can be a tool to overcome these moral and social crises by strengthening positive values and changing student behavior. Character education is a primary focus of human resource development in Indonesia, particularly in South Sulawesi. Through the implementation of the Education Report, the government aims to provide comprehensive data as a basis for informed decision-making in improving the quality of education, including aspects of student character development. The purpose of this research is (1) to look at the implementation of strengthening character education based on the results of the Education Report at the elementary school level in South Sulawesi. The research method uses a qualitative descriptive approach through observation, interviews, and document studies in several elementary schools in Makassar, Gowa, and Takalar Regency, Sulawesi, South Sulawesi; (2) Knowing the obstacles faced in its implementation. The results of the study show that: (1) the use of Education Report cards is able to help schools identify character aspects that need to be strengthened, such as discipline, responsibility, and social concern. (2) there are still obstacles in terms of teacher data literacy and limitations of follow-up programs. Thus, it is necessary to strengthen the capacity of schools in analyzing Education Report data and fostering cross-party collaboration to build a sustainable culture of character.